Influence of Supplemental Dried Whey on Broiler Performance and Cecal Flora - Kermanshahi, H.; Rostami, H. (International Journal of Poultry Science, 2006)
A study was conducted to evaluate the effects of adding levels of dried whey powder (DW) to practical-type diets on the performance and cecal micro organism of broilers. DW was used in isocaloric and isonitrogenous diets at levels of 0, 2, 4 and 8 percent and fed from 1-49 days of age. Samples of cecal contents at 7, 14 and 35th days of age were collected for counting total micro organism, coliforms and salmonella in suspension of cecal contents. Body weight gain of chickens fed 2 to 8 percent DW was improved at 49 days of age. Adding DW to the diets from 2 to 8 percent, improved feed to gain ratio at 21-42 and 42-49 days of age. Carcass weight in chickens received 2 and 4 percent DW was maximum (p< 0.05) at 49 days of age. Gastrointestinal tract weight of chickens fed DW was significantly increased (p< 0.05) when compared to control group. Total counts and coliforms of cecal contents significantly increased in broilers received DW during 0–14 days of age (p< 0.05). No salmonella colony was isolated from the samples. Findings of the present study indicate that 2-4 percent DW in the diet of broilers had beneficial effects on performance. Changes in cecal micro flora indicated an environment more hostile to salmonella establishment from 0-21 days of age.